An Overview of Hox Genes in Lophotrochozoa: Evolution and Functionality - Marco Barucca; Adriana Canapa; Maria Assunta Biscotti (Journal of Developmental Biology, 2016)
Hox genes are regulators of animal embryonic development. Changes in the number and sequence of Hox genes as well as in their expression patterns have been related to the evolution of the body plan. Lophotrochozoa is a clade of Protostomia characterized by several phyla which show a wide morphological diversity. Despite that the works summarized in this review emphasize the fragmentary nature of the data available regarding the presence and expression of Hox genes, they also offer interesting insight into the evolution of the Hox cluster and the role played by Hox genes in several phyla. However, the number of genes involved in the cluster of the lophotrochozoan ancestor is still a question of debate. The data presented here suggest that at least nine genes were present while two other genes, Lox4 and Post-2, may either have been present in the ancestor or may have arisen as a result of duplication in the Brachiopoda-Mollusca-Annelida lineage. Spatial and temporal collinearity is a feature of Hox gene expression which was probably present in the ancestor of deuterostomes and protostomes. However, in Lophotrochozoa, it has been detected in only a few species belonging to Annelida and Mollusca.